1984
DOI: 10.1002/1097-0142(19840401)53:7<1456::aid-cncr2820530705>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

High-dose cyclophosphamide. An effective treatment for advanced refractory multiple myeloma

Abstract: The Eastern Cooperative Oncology Group evaluated cyclophosphamide 600 mg/m2 intravenously daily × 4 (total dose each cycle 2400 mg/m2) as an aggressive approach to the treatment of patients with advanced multiple myeloma. The overall objective response rate is 43%. This includes a 38% response rate for all previously treated patients and a 29% response rate for patients refractory to prior therapy with cyclophosphamide. The objective response duration was 3 months and the survival of responding patients 9 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 10 publications
3
24
0
Order By: Relevance
“…Kinetic analyses done in vitro (461, and enhanced anti-BPDE cytotoxicity of 1.7-fold, relative to controls, caused by depletion of intracellular glutathione levels (17) to 10-60% of GST's K, for glutathione (0.1 mM) (22,461, were predictive of recombinant GST .rr + 'S ability to confer resistance to anti-BPDE. Significantly, values of 1.5-fold resistance relative to controls are identical with resistance values to anticancer alkylating agents observed clinically (30,31,58).…”
Section: Discussionsupporting
confidence: 70%
“…Kinetic analyses done in vitro (461, and enhanced anti-BPDE cytotoxicity of 1.7-fold, relative to controls, caused by depletion of intracellular glutathione levels (17) to 10-60% of GST's K, for glutathione (0.1 mM) (22,461, were predictive of recombinant GST .rr + 'S ability to confer resistance to anti-BPDE. Significantly, values of 1.5-fold resistance relative to controls are identical with resistance values to anticancer alkylating agents observed clinically (30,31,58).…”
Section: Discussionsupporting
confidence: 70%
“…11,12 We employed the combination of CPA and G-CSF to mobilize PBSC, because she had VADresistant disease and high-dose CPA has been shown to be effective in refractory myeloma. 13 However, she developed severe myopericarditis after high-dose CPA. Myocarditis caused by a viral infection should be considered in the differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Furthermore, it has been demonstrated that hematopoietic support is not necessary after HDCYC. 11 As HDCYC has been reported to be efficient in the treatment of refractory MM, 12 we have used it at the dose of 7 g/m 2 , either alone or followed by hematopoietic growth factors (HGF), for PBPC mobilization in 116 patients planned to receive subsequently autologous PBPC transplantation (ABPCT). The aims of this monocentric study were: (1) to evaluate in MM patients the ability of HDCYC to mobilize circulating hematopoietic progenitors and to determine the parameters associated with successful mobilization; and (2) to analyze the predictive factors for hematologic recovery following reinfusion of PBPC after myeloablative treatment in a group of MM patients mobilized with HDCYC.…”
Section: Introductionmentioning
confidence: 99%